2018
DOI: 10.3389/fendo.2018.00586
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic Effect of Punica granatum Flower Polyphenols Extract in Type 2 Diabetic Rats: Activation of Akt/GSK-3β and Inhibition of IRE1α-XBP1 Pathways

Abstract: Type 2 diabetes mellitus (T2DM) is the most common type of diabetes with more than hundreds of millions of patients worldwide. However, the medicines for treatment of T2DM are very limited. In China, Punica granatum L. flower (PGF) has been used as an anti-diabetic herb in the herbal medicine. The activity involves in improvement of insulin sensitivity. However, the underlying mechanism of action is elusive. The current study was designed to address this issue by investigating the effect of polyphenols extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 47 publications
5
17
0
Order By: Relevance
“…Blood glucose control by PPE was reported by many authors,[25] which confirm the effect of PPE in this study where its administration prior to diabetes induction keep blood glucose near-normal levels, preventing hyperglycemia adverse effects on different organs including liver.…”
Section: Discussionsupporting
confidence: 90%
“…Blood glucose control by PPE was reported by many authors,[25] which confirm the effect of PPE in this study where its administration prior to diabetes induction keep blood glucose near-normal levels, preventing hyperglycemia adverse effects on different organs including liver.…”
Section: Discussionsupporting
confidence: 90%
“…After the treatment of the diabetic rats, their body weight increased again. Similar effects were also observed by other researchers [35][36][37]. The synthetic oral hypoglycemic agents can produce a series of side effects.…”
Section: Discussionsupporting
confidence: 88%
“…Huang et al (2005) reported gallic acid as a major component of the methanolic extract of the flowers, which may be partly responsible for its anti‐hyperglycemic, as well as glucose transporter type 4 expression and insulin sensitivity modulatory effects of the extract in Zucker diabetic fatty rats. Other studies further confirmed that the ethanolic extract of the flower ameliorated diabetes‐induced hyperglycemia, insulin insensitivity, dyslipidemia and oxidative stress in STZ‐induced (Manoharan et al, 2009) and high‐fat‐diet‐induced (Tang et al, 2018) diabetic rats. In addition, polyphenol rich (HPLC: 8.3% of ellagic acid, 1.49% of gallic acid, 0.79% of pyrogallic acid, and 18.27% of tannic acid) (Yu et al, 2017) and hydroalcoholic extracts (Adnyana, Sukandar, Yuniarto, & Finna, 2014) of the leaves showed antiobesogenic activities by inhibiting pancreatic lipase activities and reducing fat intestinal absorption.…”
Section: Introductionmentioning
confidence: 76%